2012
DOI: 10.1002/jhrm.20093
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative dental injury at a tertiary care health system: An eight‐year audit of 816,690 anesthetics

Abstract: Among all complications of airway management, dental injury is the most common cause of patient complaints with medicolegal consequences. Over an 8-year period, data on dental injury were collected within a large university hospital system that included community, tertiary, and quaternary care centers. Patient characteristics were compared among all patients receiving anesthesia care using billing data collected from the same period. Of the 816,690 patients who received anesthesia care, there were 360 dental i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Pooling our findings with results obtained from the systematic review, this identified an overall adverse event rate of 0.33% with major adverse events occurring in 0.03% of upper endoscopies (see Table 4 ). These figures are comparable to anaesthesia data and suggest need for greater awareness of dental trauma as a complication of upper endoscopy and consequent steps for mitigation and management[ 12 ].…”
Section: Discussionsupporting
confidence: 60%
“…Pooling our findings with results obtained from the systematic review, this identified an overall adverse event rate of 0.33% with major adverse events occurring in 0.03% of upper endoscopies (see Table 4 ). These figures are comparable to anaesthesia data and suggest need for greater awareness of dental trauma as a complication of upper endoscopy and consequent steps for mitigation and management[ 12 ].…”
Section: Discussionsupporting
confidence: 60%
“…It is responsible for the highest number of malpractice lawsuits against anesthetists, 6 accounting for more than 33% of all complaints. 32 Surprisingly, in this study, none of the participants who had caused PADT had encountered compensation-related litigation. The state insurance system provides such treatments free of charge.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 59%
“…Some studies have found that emergency procedures have an increased PADT risk. 18,32 The anesthetists in this study stated that PADT occurred more frequently in emergency intubations, indicating that they were not aware of the at-risk elective patients.…”
Section: Ta B L Ementioning
confidence: 84%
“…7 Patients with dental restorations are 3.4 times more likely to sustain dental injury. 8 Interestingly, studies demonstrated no increase in risk for emergency intubations and even from inexperienced laryngoscopists, 9,10 although the risk is 20-fold in individuals deemed difficult to intubate. 8 Risk factors for dental injury are summarized in Table 4.…”
Section: Dental Injuries Under Anaesthesiamentioning
confidence: 99%